Application of Values Sports Through Game Traditional for Students Necessary Specifically - Wijayanti, Dwi Gansar Santi; Yuwono, Cahyo; Nurharsono, Tri; Billiandri, Bhayu; Maharani, Salsabilla Brita; Effendi, Muhammad Zufar Hafizh; Fadholi, Faisal Gosi (Jurnal Abdimas, 2023)
The aim of this community service activity is to introduce and apply the sports values contained in traditional games to students with special needs. The implementation method used is a demonstration with 5 stages, namely (1) planning, (2) screening, (3) implementation, (4) evaluation, (5) reporting. The result of this activity is that students with special needs are enthusiastic about playing traditional games. The participants carried out every instruction given. So, you don't feel burdened when doing physical activity. The game for mentally retarded students is dakon, this game is used to train students' sense of touch and memory. For deaf and speech impaired students there are Bakian games, rope stilts and beam running, this aims to build solidarity through communication and train coordination of body parts. The games of snakes and ladders and jumping rope are applied to mentally retarded students, so that mentally retarded students are able to train their sense of trust and ultimately be able to socialize with the people around them. Meanwhile, students with physical impairments are introduced to simple educational games, namely sticks and srempeng. And autistic students are given traditional games that honor their imagination. Traditional games are full of sporting values, such as: sportsmanship, respect, cooperation, responsibility, honesty, caring for the rules, ability to overcome problems, understanding, interacting with other people, fair play, sharing, self-respect. So, it can be concluded that traditional game activities can be used as a medium to apply sports values to students with special needs. Because they do it willingly and without any coercion.